Comparison of Three Bed Bug Management Strategies in a Low-Income Apartment Building - Changlu Wang; Kurt Saltzmann; Timothy Gibb; Gary Bennett (Insects, 2012)
Bed bug (Cimex lectularius L.) infestations are currently controlled by a variety of non-chemical and chemical methods. There have been few studies on the comparative effectiveness of these control techniques. We evaluated three bed bug management strategies in an apartment building: (1) non-chemical methods only (n = 9); (2) insecticides only (n = 6); and (3) integrated pest management including both non-chemical methods and insecticides (n = 9). The apartments were one-bedroom units occupied by seniors or people with disabilities. Bed bug numbers in each apartment were determined by visual inspection and/or installing intercepting devices under bed and sofa legs. The median (min, max) bed bug counts in the non-chemical methods only, insecticides only, and integrated pest management (IPM) treatment were: 4 (1, 57), 19 (1, 250), and 14 (1, 219), respectively prior to the treatments. The apartments were retreated if found necessary during biweekly to monthly inspections. After 10 weeks, bed bugs were found to be eliminated from 67, 33, and 44% of the apartments in the three treatment groups, respectively. The final (after 10 weeks) median (min, max) bed bug counts in the non-chemical methods only, insecticides only, and IPM treatment were: 0 (0, 134), 11.5 (0, 58), and 1 (0, 38), respectively. There were no significant differences in the speed of bed bug count reduction or the final bed bug counts. Lack of resident cooperation partially contributed to the failure in eliminating bed bugs from some of the apartments. Results of this study suggest that non-chemical methods can effectively eliminate bed bugs in lightly infested apartments.